Segmental epidural anesthesia for percutaneous kyphoplasty: Comparison with general anesthesia - Apan, Alparslan; Çuvaş Apan, Özgün; Köse, Emine Arzu (Tubitak Scientific, 2016)
Background/aim: This is a feasibility study evaluating whether segmental epidural anesthesia is an alternative anesthetic approach to general anesthesia for percutaneous kyphoplasty. Materials and methods: After ethics committee approval was obtained, 52 ASA class I–III patients scheduled for elective, single-level percutaneous kyphoplasty were recruited. The patients were divided into two equal groups. In Group E (Group Epidural) segmental epidural anesthesia was performed using the loss of resistance technique with saline. In Group G (Group Control) general anesthesia was performed. Hemodynamic parameters, intraoperative and postoperative analgesic requirements, visual analogue scale (VAS) scores, length of stay in the postanesthesia care unit (PACU), and complications were recorded. Results: Hemodynamics were similar between the two groups. Postoperative analgesic requirement was significantly higher in Group G than in Group E (P < 0.004). VAS scores were significantly lower in Group E than in Group G (P < 0.05). Time to first pain experience at the first postoperative 4 h was significantly longer and length of stay in the PACU was significantly shorter in Group E than in Group G (P < 0.001). Conclusion: Segmental epidural anesthesia is a safe anesthetic technique for percutaneous kyphoplasty. This technique offered advantages over general anesthesia in terms of postoperative analgesia, analgesic consumption, early recovery, and short PACU stay. Therefore, it should be considered a suitable anesthetic technique in patients undergoing single level percutaneous kyphoplasty.
Keywords: General Anesthesia; Epidural Anesthesia; Kyphoplasty; Neurosurgery